How do you simplify ( 7 - sqrt7)/(10 +sqrt3)?

2 Answers
Dec 8, 2017

There is not much you can do. Only put square root to the top.

Explanation:

(7−√7)/(10+√3)*(10-sqrt(3))/(10-sqrt(3))=

=(70-10sqrt(7)+sqrt(21)-7sqrt(3))/(10^2-(sqrt(3))^2)=

=(70-10sqrt(7)+sqrt(21)-7sqrt(3))/97

Dec 8, 2017

=(70-7sqrt3-10sqrt7+sqrt21)/97

Explanation:

To simplify this expression we rationalise the denominator. That is multiply top and bottom by a term that will remove the square root.

We make use of the difference of squares identity

a^2-b^2=(a+b)(a-b)

(7-sqrt7)/(10+sqrt3)=(7-sqrt7)/(10+sqrt3)xx(10-sqrt3)/(10-sqrt3)

=(70-7sqrt3-10sqrt7+sqrt21)/(100-3)

=(70-7sqrt3-10sqrt7+sqrt21)/97